Water Management Using System Dynamics Modeling in Semi-arid Regions - Hamid Reza Nassery; Rouhollah Adinehvand; Abdalrahim Salavitabar; Reza Barati (Civil Engineering Journal, 2017)
Quantitative control and safe exploitation of water resources are crucial components for the sustainable development of any region due to increasing water scarcity, especially in arid and semiarid regions. A proper water resources management program of the Tabriz plain is necessary because of the groundwater excessive exploitation and the surface water limitations. The present study aims to develop a system dynamics (SD) model not only to identify safe groundwater level fluctuations and exploitation but also to determine the amount of supply and deficits of municipal-industry and agricultural uses by considering various water management strategies. The integrated water resources including surface and groundwater resources were included in the analyses. The considered alternatives are the development of sewage collection networks, enhancement of agricultural efficiency, climate changes effects, artificial recharge and changes of the allocation of the surface and groundwater in supplying water needs. SD modeling application showed that if the current management policy was continued, the users will face a crisis of the water supply for various uses in the future. Increase in agricultural efficiency, reducing in groundwater extraction and artificial recharge in Tabriz plain must be considered to prevent the crisis. The current model provides a better understanding of the principal challenge of balancing supply and demand with regards to drastic changes of water resources in arid or semiarid regions.